Resurrection of Lethrinus scoparius Gilchrist & Thompson, 1908 (Perciformes: Lethrinidae), from South African waters - Holleman, Wouter; Gouws, Gavin; Glass, Jessica R; Mann, Bruce Q (Zootaxa, 2022)
Lethrinus nebulosus (Forsskål, 1775) is distributed throughout the Indian Ocean, Indonesia and the West-central Pacific. Given recent evidence suggesting two cryptic species of L. nebulosus in the southwestern Indian Ocean, we implemented a multispecies coalescent approach using nuclear and mitochondrial DNA loci and conducted Bayesian tests of species delimitation. One population extends from southern Mozambique to Kenya, and the other from northern KwaZulu-Natal (South Africa) southwards, with a zone of overlap between them. This study confirms that the South African ‘population’ can be identified as a separate species, previously identified as Lethrinus scoparius Gilchrist & Thompson, 1908, and can be distinguished from L. nebulosus by live and fresh colouration and with genetic data, but not consistently by morphometric or meristic parameters, other than in preorbital length cf. head length. Lethrinus scoparius is resurrected and redescribed herein.